Fieldwork and footnotes : studies in the history of European anthropology - Vermeulen, Han F., 1952-; Alvarez Roldán, Arturo, 1963- (Routledge, 1995)
The history of anthropology has great relevance for current debates within the discipline, offering a foundation from which the professionalisation of anthropology can evolve. The authors explore key issues in the history of social and cultural anthropological approaches in Germany, Great Britain, France, The Netherlands, Sweden, Poland, Slovenia and Romania, as well as the influence of Spanish anthropologists in Mexico to provide a comprehensive overview of European anthropological traditions.
"European Association of Social Anthropologists."
Keywords: Anthropology -- Europe -- History.; Ethnology -- Europe -- History.; Anthropologie -- Europe -- Histoire.; Ethnologie -- Europe -- Histoire.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Anthropology; Ethnology; Europe; Electronic books.; History